CRITICAL DISCOURSE ANALYSIS OF INTIMATE PARTNER VIOLENCE IN INDONESIAN ONLINE NEWS DURING THE COVID-19 PANDEMIC - Perangin-angin, Alemina Br.; Nasution, Ely Hayati; Andayani, Widya (Annual International Conferences on Language, Literature, and Media, 2022)
The article concerns a critical discourse analysis (CDA) of women as subjects of violence in Indonesia during the current Corona Virus 19 (COVID19) pandemic. Through the framework of critical discourse analysis, it aims to determine how news online presents an overview and perspectives on the problem of women who experience intimate partner violence during the current pandemic. The research design chosen is qualitative research with the tools of content analysis. Critical discourse analysis describes the language employed to convey meaning in the content of BBC news online. While the BBC's online news online highlighted the existence of gender symmetry and stereotype abusers throughout the epidemic experienced by women, the BBC's online news online was able and daring enough to highlight the marginalization of women.